Heuristic solution for the acoustic radiation of a moving monopole in an inhomogeneous and moving atmosphere. Application to aircraft noise - Kayser Bill; Dragna Didier; Blanc-Benon Philippe (Acta Acustica)
A coupled approach is proposed for predicting sound radiation from a monopole in arbitrary motion in a moving and inhomogeneous atmosphere. It is based on a heuristic model proposed in the literature for sound radiation by a moving source in a homogeneous atmosphere at rest above an absorbing ground and a ray-tracing code, which takes into account meteorological effects. Validation of the model is performed with a reference three-dimensional finite-difference time-domain solution of the linearized Euler equations for several test-cases with different source trajectories and atmospheric conditions. We show that neglecting convective amplification or the source motion between the emission and reception times can lead to significant errors in the predictions. Finally, an application case for aircraft noise is presented. The importance of ground and meteorological effects on the sound pressure levels is highlighted.